PROBLEMATIC ISSUES ABOUT THE IMPLEMENTATION OF INTERNATIONAL TREATIES IN THE CRIMINAL LEGISLATION OF THE REPUBLIC OF KAZAKHSTANPROBLEMATIC ISSUES ABOUT THE IMPLEMENTATION OF INTERNATIONAL TREATIES IN THE PROBLEMATIC ISSUES ABOUT THTION OF INTERNATIONAL TREATIES I OF INTERNATIONAL TREATIES IN THE CRIMINAL LEGISLATION OF THE REPUBLIC OF KAZAKHSTANN THE PROBE IMPLEMENTALEMATIC ISSUES ABOUT THE IMPLEMENTATIONCRIMINAL LEGISLATION OF THE REPUBLIC OF KAZAKHSTANCRIMINAL LEGISLATION OF THE REАҚСТАН - Zhanat Askarovna, Мамитова (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
This article explores the essence of and issues in the implementation of international legal norms into law legislation